MANAJEMEN LIMBAH PABRIK KARET DALAM RANGKA PENURUNAN KADAR BOD (BIOLOGICAL OXYGEN DEMAND) - Asramid Yasin (Jurnal Green Growth dan Manajemen Lingkungan, 2018)
Abstract The research is aimed at gaining a description of waste rubber factory management, Perkebunan Nusantara VIII Company Kebun Cikumpay in Purwakarta Province of West Java to Reduction of Rate BOD (Biological Oxygen Demand). The research used a theoretical descriptive method. Data have been collected by observation, interview and documents. The results showed that the reduction of rate BOD caused by the factory carried out the wastewater management by applying clean production concept for example: (1) minimizing waste with lessening wastewater volume, using of the ditch through a closed pipe, rubber trap, chemicals raw materials namely New Nicola (liquid smoke) and Food Grade with lower of hazard, more efficient and more cheap. (2) reusing of waste for sale as by products and (3) wastewater treatment with using of IPAL the consisted of 2 anaerobic and 3 facultative ponds. Keywords: wastewater management of rubber and reduction of rate BOD